Investigation of the role of irisin and FABP4 in iron deficiency anemia - Selmanoğlu, Ahmet; Akarsu, Saadet; Aydin, Suleyman (My University, 2025)
Objective: Anemia is defined as a condition in which the hemoglobin level is lower. Irisin (Ir) was a muscle-associated factor. Fatty acid- binding proteins (FABP) are involved in intracellular fatty acid transport. The study aimed to explore whether Ir and FABP4 levels might be linked to symptoms such as coldness, fatigue, and learning difficulties with Iron deficiency. Material and Methods: Our study evaluated the effects of these three periods of iron deficiency, along with a control group, on serum and urine Ir, as well as FABP4 levels, both before and after iron treatment. Results: In this study, median serum Ir levels exhibited statistically significant differences between the patient and control groups, with lower levels observed in the patient groups before treatment (p=0.040, p<0.001 and p<0.001). After treatment, a significant increase was noted in median serum Ir levels across all patient groups (p=0.003, p=0.023 and p=0.014). Conclusion: In our study, we found that the feeling of coldness and decreased cognitive functions seen in iron deficiency may be related to serum Ir level.
Keywords: Iron deficiency; FABP4; Iron deficiency anemia; Irisin